GAMBARAN PENGETAHUAN ORANG TUA TENTANG KESEHATAN REPRODUKSI REMAJA RETARDASI MENTAL - Nur Handayani; Dwi Yati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Adolescence is a transition between childhood and adulthood, where changes and developmentoccur, including the development of reproductive organs. Reproductive health problems that maybe experienced by adolescents include unwanted pregnancy, sexually transmitted diseases, and theproblem of limited access to information. The introduction of the reproductive system foradolescents is the responsibility of parents, so parents must have sufficient knowledge aboutadolescent reproductive health.The purpose of this study was to determine the description ofparents' knowledge about adolescent reproductive health mental retardation in SLB C WiyataDharma 2 Sleman.This research is a quantitative descriptive study with cross sectional design.The study was conducted in June 2019. The population in this study were adolescent parents ofmild or moderate mental retadation in SLB C Wiyata Dharma 2 Sleman as many as 43respondents. The sample consisted of 43 parents, taken with a total sampling technique. Datacollection tool is a questionnaire. Data were then analyzed using frequency distribution and crosstabulation.The results showed that the majority of respondents had good knowledge as much as(74.4%). Where respondent who have goog knowledge are mostly aged 36-45 years (35%), witheducation background high school / vocational (48.9%), work privately (30.2%) and getinformation about reproductive health (72.1%), most information obtained from the internet(40%).Parents' Knowledge of Adolescent Reproductive Health in SLB C Wiyata Dharma 2 Slemanin the good category.